Cu single-atoms embedded in porous carbon nitride for selective oxidation of methane to oxygenates. Issue 93 (9th November 2020) - Wu, Bo; Yang, Ruoou; Shi, Lei; Lin, Tiejun; Yu, Xing; Huang, Min; Gong, Kun; Sun, Fanfei; Jiang, Zheng; Li, Shenggang; Zhong, Liangshu; Sun, Yuhan
Abstract : Cu-SAs/C3 N4 with Cu–N4 as active sites exhibited high activity and high oxygenate selectivity for methane conversion at ambient temperature. Abstract : Cu single atoms embedded in the C3 N4 (Cu-SAs/C3 N4 ) matrix exhibited high activity with 95% oxygenate selectivity for the direct conversion of methane at ambient temperature. The presence of abundant anchoring sites in C3 N4 led to highly dispersed Cu–N4 moieties, which were suggested to be the underlying active sites for methane conversion.